Attitudes Toward Seeking Professional Psychological Help: Factor Structure and Socio-Demographic Predictors - Picco, Louisa; Abdin, Edimanysah; Chong, Siow Ann; Pang, Shirlene; Shafie, Saleha; Chua, Boon Yiang; Vaingankar, Janhavi A.; Ong, Lue Ping; Tay, Jenny; Subramaniam, Mythily (Frontiers in Psychology, 2016)
Attitudes toward seeking professional psychological help (ATSPPH) are complex. Help seeking preferences are influenced by various attitudinal and socio-demographic factors and can often result in unmet needs, treatment gaps and delays in help seeking. The aims of the current study were to explore the factor structure of the ATSPPH short form (-SF) scale and determine whether any significant socio-demographic differences exist in terms of help-seeking attitudes. Data were extracted from a population-based survey conducted among Singapore residents aged 18-65 years. Respondents provided socio-demographic information and were administered the ATSPPH-SF. Weighted mean and standard error of the mean were calculated for continuous variables, and frequencies and percentages for categorical variables. Confirmatory factor analysis and exploratory factor analysis were performed to establish the validity of the factor structure of the ATSPPH-SF scale. Multivariable linear regressions were conducted to examine predictors of each of the ATSPPH-SF factors. The factor analysis revealed that the ATSPPH-SF formed three distinct dimensions: ‘Openness to seeking professional help’, ‘Value in seeking professional help’ and ‘Preference to cope on one’s own’. Multiple linear regression analyses showed that age, gender, ethnicity, marital status, education, and employment status were significantly associated with the ATSPPH-SF factors. Population subgroups that were less open to or saw less value in seeking psychological help should be targeted via culturally appropriate education campaigns and tailored and supportive interventions.